Analisis Evaluasi Model Quantum Learning Dalam Pembelajaran Anak Inklusi Di Madrasah Ibtidaiyah: Evaluation Analysis of the Quantum Learning Model in Inclusive Education at Madrasah Ibtidaiyah - Sholihah, Maidatus; Lailiyah, Siti (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The acceleration of inclusive education requires learning models and evaluation systems that are fair, adaptive, and responsive to students’ diverse needs, particularly children with special needs in Madrasah Ibtidaiyah (MI). Although Quantum Learning (QL) is widely recognized as a multisensory, learner-centered instructional model, existing studies have primarily focused on learning effectiveness while paying limited attention to adaptive, individualized evaluation in inclusive settings. This study aims to examine the characteristics of Quantum Learning in inclusive MI classrooms and to formulate an adaptive evaluation framework aligned with inclusive education principles and 21st-century learning demands. Using a literature review design with a conceptual content analysis approach, this study synthesizes reference books and reputable journal articles indexed in Scopus and SINTA, focusing on Quantum Learning, IEP-based inclusive assessment, differentiated assessment, and the Deep Learning paradigm. The findings reveal that while QL demonstrates strong pedagogical relevance for inclusive classrooms, it lacks a structured adaptive evaluation framework. Accordingly, this study proposes a Quantum Learning Adaptive Evaluation Framework that integrates QL pedagogy, inclusive assessment principles, and Deep Learning–based evaluation, emphasizing deep understanding and concept transfer. This framework highlights the importance of embedding evaluation within instructional design to enhance the quality of inclusive learning in MI.